(untitled) (مجلة المنصور, 2023)
Field programmable gate array (FPGA) are integrated circuits which can be user customized to implement arbitrary digital functions. In this paper, simple and extendable microprocessor is designed and implemented, connected with small extendable read only memory (ROM) which can be used to store the instruction codes of the programs. The design and implementation of the microprocessor system have been done by using very high speed descriptive language (VHDL), and its implementation on field programmable gate array (FPGA) by using the synthesis tools of (Xilinx foundation series 4.1i program), while simulation carried out in ModelSim5.4 environment. The flexibility, low cost, and real time operation are the main features taken into consideration for the proposed design. Several programs are implemented and simulated, which will be demonstrated through several examples.